Assessing Long-Term and Short-Term Relationships on Company Profits Through The Company’s Internal - Emalia Putri Anggraeni; Dini Rahmayanti (Mutanaqishah: Journal of Islamic Banking, 2023)
A company must generate profits to survive. In carrying out investments, investors will undoubtedly review when investing in companies based on the company's rate of return on capital. The purpose of the research aims the short-term and long-term relationship between the Current Ratio, Debt To Equity Ratio, Working Capital Turnover, and Net Profit Margin to Return On Equity. This study will use the VECM data panel model for companies that are members of the Jakarta Islamic Index for the 2016-2022. The results here show that the CR, DER, and WCTO have a significant effect on ROE, but not the NPM, which has no significant effect on ROE. The implications of the research results show that ROE, CR, DER, ECTO, and NPM have an influencing relationship with one another. The transformation of one of the variables affects the other variables.